2009
DOI: 10.1007/s00035-009-0056-2
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variation among Iberian communities of the exotic halophyte Cotula coronopifolia

Abstract: The exotic annual forb Cotula coronopifolia has locally invaded salt marsh communities naturally dominated by Spergularia marina along large parts of the Iberian coastline. While the floristic composition of C. coronopifolia dominated communities on the Atlantic coast of northern Portugal has already been described, this information was missing for the southern part of the country. We carried out a phytosociological study at 21 sites along the south-western and southern coast of mainland Portugal to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 14 publications
1
10
1
Order By: Relevance
“…The results indicated that geographic region had significant influence on the populations' genetic diversity. These results correspond with the report of Bergmann et al that large differences among geographic isolates of duckweeds were found when they selected superior duckweed (Lemnaceae) genotypes for the utilization of nutrients in animal wastes [32], and the geographic differentiation of some other plants [33][34][35][36]. Different communities may have resulted in the significant genetic differentiation between duckweed populations; local selective forces may greatly affect genetic diversity within duckweed populations.…”
Section: Geographic Differentiation Of Duckweedsupporting
confidence: 90%
“…The results indicated that geographic region had significant influence on the populations' genetic diversity. These results correspond with the report of Bergmann et al that large differences among geographic isolates of duckweeds were found when they selected superior duckweed (Lemnaceae) genotypes for the utilization of nutrients in animal wastes [32], and the geographic differentiation of some other plants [33][34][35][36]. Different communities may have resulted in the significant genetic differentiation between duckweed populations; local selective forces may greatly affect genetic diversity within duckweed populations.…”
Section: Geographic Differentiation Of Duckweedsupporting
confidence: 90%
“…Disturbances, such as tsunamis and floods that frequently occur in Chile, may also be important (Fariña & Camaño, 2012). Cotula coronopifolia, for example, is found to be associated with tsunamis disturbance, and also colonizes gaps in tall perennial vegetation (Costa, Neto, Ars enio, & Capelo, 2009 Bertness, Cough, & Shumway, 1992;Bertness & Ellison, 1987). In arid higher latitudes, lowered high-marsh salinity stress due to increased precipitation allows S. fruticosa to occupy the entire marsh.…”
Section: Discussionmentioning
confidence: 99%
“…The presence is estimated in percentages of a species and classified according to a chosen scale into a set of 'classes of presence'. The classes were defined as follows (Costa et al, 2009): r (< 6%); + (6-10%); I (11-20%); II (21-40%); III (41-60%); IV (61-80%); V (> 81%).…”
Section: Vegetation Datamentioning
confidence: 99%